Food plant diversity determines home range area and formation of a new family group of the world’s rarest primate - Wang, Lu; Li, Yousheng; Cui, Jie; Zhang, Hui; Gong, Wenfeng (Frontiers in Environmental Science, 2022)
Global primates are in endangered and thus it is important to know the determinants of primate population dynamics. It is widely reported that, food plant diversity and nutrients are key determinants of many primate population dynamics. However, it remains unknown whether this can be applied to explain population dynamics of Hainan gibbon (Nomascus hainanus), the world’s rarest primate. Recently two individuals move out of one family group (group C) and go across more than 9 km to form a new family group (group E) and thus provide a perfect chance to quantify whether food plant diversity and nutrients can determine Hainan gibbon’s formation of new family group. Here we used plot-survey to compare the differences in food plant diversity (species richness and abundance) and nine leaf nutrients (leaf water content, total soluble sugar, vitamin C, calorific value, crude fat, crude protein, crude fiber, Zn and Fe) between group C and group E. We found that plant diversity in group E was indeed higher (1.35-1.41 times) than that in group C. Moreover, in both group C and E, food plant diversity within the home range was also higher (1.4-1.6 times), compared to that out of the home range. However, both cases cannot be witnessed for all leaf nutrients. Results of principal component analysis reveal that food plant species between group C and E are all significantly separated by food plant diversity but not leaf nutrients. Food plant species between within and out of the home range for both group C and E could also be significantly separated by food plant diversity but not for all leaf nutrient. In conclusion, food plant diversity determined the formation of new family group of Hainan gibbon. Choosing high food plant diversity was also one key motivation for Hainan gibbon to select their home range.